Revision of the genus Coeliccia Kirby in Borneo part III: Two new species from the C. membranipes–group from Sarawak and Brunei (Odonata: Zygoptera: Platycnemididae) - Dow, Rory A. (Zootaxa, 2020)
Coeliccia junis sp. nov. (holotype male from Borneo, Sarawak, Bintulu Division, Planted Forest Project, Bukit Mina Wildlife Corridor, “Day 4” stream near Bukit Nyegoh and Bukit Jugam, near small brown water pool, 10 viii 2018, deposited in the Naturalis Biodiversity Center, Leiden, the Netherlands) and Coeliccia roberti sp. nov. (holotype male from Borneo, Sarawak, Miri Division, Lambir Hills National Park, small stream on Oil Well Trail, 22 iv 2011, deposited in the Naturalis Biodiversity Center, Leiden, the Netherlands) are described from Borneo. Both new species belong to the Coeliccia membranipes–group and bring the number of named species known from the group from Borneo to nine and the total number of named species from Borneo currently placed in Coeliccia to 15. Coeliccia junis is only known from a small area in Sarawak, C. roberti is also known from Brunei. Both species are considered likely to be closely allied with C. macrostigma Laidlaw.